Fabrication of display unit for electrical and electronic wire harness of single cylinder four stroke engine for teaching purpose - Mohd Hassnun Saiffuddin, Mohd Mustafa (2012)
This project is about to design the display unit for the electric and electronic wire harness of the motorcycle for the teaching. Its purpose is to ease the user to study about the wire harness in the motorcycle without need to tear down the whole bike. This project component is base on single cylinder four stroke engine of Yamaha FZ 150i which is using the injection technology. This project is design base on the sketching from the computer software and manual sketching to place the electronic component of the motorcycle which will ease the user to understand the arrangement of the wire harness in the motorcycle. Understanding the problem of user to identify each component, it has been label and each of them had been described as simple as possible. Each material of the project is using the tough and rigid to built the chassis and resist to any force. It also can be modified for the further development in the future. As the result it has down the cost and satisfied the user about the project purpose.